Current issues of modern migration policy in Russia - A. I. Velichko (Вестник университета)
Current issues of modern migration policy of Russia have been analyzed. It reflects the current state and trends of migration processes in the country on the basis of official statistical data from 2023-2024. On the basis of empirical data and information, the risks and dangers of the modern migration state in Russia have been actualized, and recommendations for improving the system have been developed. The article concludes that Russia’s migration policy is characterized by a rather loyal and liberal approach, which makes it possible to trace relatively open and “easy” opportunities for foreign citizens to arrive and stay in the state territory, in particular, for their labor and other economic activities. The policy is aimed at filling demographic issues and filling the labor market with relatively cheap workers from Central Asian countries without considering the consequences of socio-cultural adaptation and integration of foreign citizens into Russian society. The new migration policy paradigm proposes legal, administrative, and organizational measures to compensate for these issues.